Astragalus Oral Solution Ameliorates Allergic Asthma in Children by Regulating Relative Contents of CD4+CD25highCD127low Treg Cells - Wang, Wei; Jing, Wei; Liu, Qingbin (Frontiers in Pediatrics, 2018)
Objective To explore the effects of Astragalus oral solution (AOS) on allergic asthma in children by investigating relative contents of CD4+CD25highCD127low Treg cells. Methods The contents of Astragaloside A in AOS were detected by using HPLC. Eighty children with allergic asthma were recruited from February 2016 to June 2017, and randomly assigned into the control group (received placebo, 0.1% quinine chloride in deionized water, daily) and the AOS group (received 10 mL AOS daily). After six-month treatment, therapeutic results were compared between the two groups. Serum levels of IL-10 and TGF-beta, Th1 cytokines (IL-2 and IFN-γ), and Th2 cytokines (IL-4 and IL-6) were measured by using ELISA kits. Relative contents of CD4+CD25highCD127low Treg cells were determined by using flow cytometry. Results Astragaloside A was the main ingredient of AOS with 0.216 ± 0.027 mg/mL from six-batch samples. After six-month therapy, the AOS group showed improved forced expiratory volume in 1 s (FEV1) and the Pediatric Asthma Quality of Life Questionnaire (PAQLQ) scores compared with the control group (P<0.05)．Serum level of IL-10 was higher and the levels of TGF-beta, Th1 cytokines (IL-2 and IFN-γ), and Th2 cytokines (IL-4 and IL-6) were lower in the AOS group than in the control group (P<0.05). AOS treatment increased the percentage of gated CD4+ T cells, CD4+CD25+ T cells, CD4+CD25high Treg cells, CD4+CD25+FoxP3+ Treg cells and CD4+CD25highCD127low Treg cells when compared with the control group (P <0.05). Conclusions Astragaloside A was the main component of AOS, and AOS ameliorated allergic asthma in children by regulating relative contents of CD4+CD25highCD127low Treg cells.